STRES KERJA DAN MOTIVASI KARYAWAN LINI DEPAN SERTA PENGARUHNYA TERHADAP KEPUASAN KERJA: KAJIAN EMPIRIS PADA BEBERAPA PERUSAHAAN JASA SUB SEKTOR INDUSTRI KREATIF - Nugroho J. Setiadi; Gina R. Miftah; Kristian Suhartadi Widi Nugraha (UNEJ e-Proceeding)
The aims of the study is to examine the notion that work stress and motivation have a significant impact on employee job satisfaction. In this study, 148 front office employees from some service companies of creative industries participate to the study. Data collection is done by direct observation and interviews. Analyses were performed using factor analysis, reliability, descriptive, classical-assumption test prior to the multiple regression analysis. The results showed that the job stress and motivation has a significant impact on employee job satisfaction. Another interesting finding of the study is the emergence of stress that is caused by many factors, including the burden of the task given by the management that can not be resolved in time, the workload is too heavy given by the company for employees and must be resolved as soon as possible.